Interpretation of angle-of-arrival measurements in the lower atmosphere using spaced antenna radar systems - Chau Chong Shing, Jorge Luis (1998)
On the basis of scattering theory, we present four different contributions to angle-of-arrival (AOA) measurements using spaced antenna (SA) radar systems. We show that the measurement of the scattering parameters is needed to estimate most AOA contributions (e.g., tilt angle of layers). We analyze a general SA system (i.e., receiving antennas not necessarily symmetrically placed about the transmitter) and show, theoretically, that such systems can be used for vertical velocity corrections without explicitly knowing the scattering parameters (e.g., correlation lengths). The theoretical AOA expressions are compared with lower atmospheric data (3–21 km) obtained with the Jicamarca VHF radar system in Perú. We compare the AOAs obtained by a time and a frequency domain method, giving both methods essentially the same information. While the results are comparable, frequency domain AOAs tend to exhibit more outliers. From examination of time series of these AOA measurements, we find some short, but predominantly long-period oscillations (12 hours) with amplitudes of -1.